True, reliable and valid? : data and community experience in the case of the janitorial service social audit - Rossouw, Jared (Department of Sociology, 2016)
Across South Africa, poor and working class people are rising up in violent protest because of poor delivery of basic services. The frustration and rage is palpable and points to the high expectations that South Africans have in the post-apartheid state. At the same time municipalities are struggling to facilitate meaningful participation. As a result, citizens are using creative new ways to engage government in invented participatory spaces. Social audits aim to empower communities to gathering evidence and verify the delivery of basic services and present their findings at a public hearing and have the potential to valorise and legitimise community experience, making it legible to government officials, ensuring participation, accountability and the realisation of human rights. I present a case study of a social audit conducted by the Social Justice Coalition in the City of Cape Town on a janitorial service for full flush toilets in informal settlements. Given the City's previous vociferous attacks on the process, I focus on attempts to improve the legitimacy of the social audit through improvements to the data collection method. I describe, the messy reality of data collection and how despite these efforts, the City officials followed a clear agenda to deny the findings, attack the data and blame the residents for poor service delivery. Although there is some evidence that the social audit had some impact in terms of advocacy, I argue that our reliance on data resulted in lost opportunities for capturing and articulating community knowledge and experience. It is hard to know whether this was inevitable given the City's track record on meaningful participation, leaving us with unanswered questions as to how social auditing can result in accountability and justice. Despite this foundations have been laid for the growth of social audits nationally, presenting further opportunities for comparative scholarship and case studies.